IMPACT OF HRM PRACTICES ON EMPLOYEE SATISFACTION IN BANKING SECTOR IN CHITTOOR DISTRICT - Suresh, P.; Reddy, T.Narayana (International Journal of Engineering Technologies and Management Research, 2017)
Employee satisfaction plays a key role on both the individual and organisation. Employee satisfaction will result in improving organisation productivity. The present study is carried out to comprehend the effect of HRM Practices in banking sector. This study is based on both primary and secondary data, reviewing the literatures related to HRM Practices, employee satisfaction, in banks of chittoor district. The objective of the study focuses on understanding Effect of HRM practices on Employee satisfaction banking organizations on employee satisfaction towards organization. The study results revealed that there is significant impact of HRM practices on employee satisfaction.